Modelling Central Bank Independence and Inflation: Deus Ex Machina? - Dumiter, Florin; Brezeanu, Petre; Radu, Claudia; Turcaș, Florin (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Central bank independence represents the core element of assessing the complex relationship between government and central bank, having at background the fundamental issue of a free monetary policy decision-making process from the hands of the political circle. However, central bank independence is a multilevel concept within some social, economic and behavioral implications both for the central banks and for the society at whole. Central bank independence is needed in order to establish an autonomous central bank with a high degree of freedom in choosing its’ instruments, objectives, techniques and tactics. Moreover, a high degree of transparency for the public disclosure and monitoring of central bank operation and transaction is needed for the social barometer of the central bank. Consequently the central bank must have a high degree of accountability and responsibility vis – á – vis of the most democratic institution, i.e. Parliament. In this article it is presented a comprehensive study regarding the complex relationship between central bank independence and inflation by modeling these two monetary policy panacea, in order to make a fine tuning regarding the causal relationship established in a heterodox manner.